2014
DOI: 10.1103/physreve.90.046101
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Dependence of asymptotic decay exponents on initial condition and the resulting scaling violation”

Abstract: We present the mapping relation between a one-dimensional conserved lattice gas model and a two species reaction A+B→0. From the kinetics of A+B→0, we show that the anomalous critical decay of an order parameter in the conserved lattice gas model results from finite-size effects induced by the domain structure for random initial conditions where the scaling relation z=ν∥/ν⊥ is violated. A simple initial condition satisfying the scaling relation is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, for ρ < 1, total mass is smaller than the number of empty sites (ρ A (0) < ρ B (0)), so the system eventually falls into one of absorbing states consisting of empty sites and inactive sites of m = 1. As a result, in terms of A + B → 0 reaction, the SCA model undergoes the crossover at ρ = 1 from the kinetics of ρ A (0) > ρ B (0) to that of ρ A (0) = ρ B (0) for ρ → 1 + as shown for conserved lattice gas (CLG) model in d = 1 [49,50].…”
Section: ω = 1 Andmentioning
confidence: 90%
See 2 more Smart Citations
“…However, for ρ < 1, total mass is smaller than the number of empty sites (ρ A (0) < ρ B (0)), so the system eventually falls into one of absorbing states consisting of empty sites and inactive sites of m = 1. As a result, in terms of A + B → 0 reaction, the SCA model undergoes the crossover at ρ = 1 from the kinetics of ρ A (0) > ρ B (0) to that of ρ A (0) = ρ B (0) for ρ → 1 + as shown for conserved lattice gas (CLG) model in d = 1 [49,50].…”
Section: ω = 1 Andmentioning
confidence: 90%
“…It is shown that the dynamics of active masses is eectively considered as A + A → A reaction for ω < ω 0 (≈ 0.5), and A + B → 0 reaction at ω = 1. Since the reproduction of particles and the mutation to the other species are not allowed in both reactions [47][48][49][50], APTs cannot take place for ω < ω 0 and ω = 1 in the SCA model. For ω 0 ω < 1, however, APT is shown to occur due to the competition of aggregation and chipping processes, and ρ c continuously increases with ω.…”
Section: J Stat Mech (2018) 113204mentioning
confidence: 99%
See 1 more Smart Citation